2023
DOI: 10.3126/nje.v13i2.52766
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Covid-19 on the mental health of the people in the Indian subcontinent: A scoping review

Russell Kabir,
Ancy Chandrababu Mercy Bai,
Haniya Zehra Syed
et al.

Abstract: Background: Indian subcontinent  has high mental heath burden and low resoueces to cope the mental health challenges. Assessment of impact of Covid-19 pandemic on the mental mental healthwould help to prioratize the resource allocations. We aimed to assess the impact of COVID-19 on the mental health of people in the Indian subcontinent. Methods: We followed PRISMA guidelines and made a systematic serach in PubMed, Scopus, and Embase to identify the original studies assessing mental health conditions during Cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…On the other hand, countries with low- and middle-income category (LMIC) like countries in Indian Subcontinent (Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka) struggled a much while facing the pandemic due to death, physical morbidity, services burden during the pandemic. One recent scoping review identified that the prevalence of anxiety, depression, and stress widely varies based on the study methods, study settings, phase of the pandemic and instrument used to assess the measures ( 3 ). It found the prevalence of anxiety varied from 2.5% in North India to 53% in Bangladesh, depression varied from 3.5% in North Indian slum to 29.8% in Pakistan, and stress related symptoms varied from 18.3% in Pakistan to 59.7% in Bangladesh ( 3 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, countries with low- and middle-income category (LMIC) like countries in Indian Subcontinent (Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka) struggled a much while facing the pandemic due to death, physical morbidity, services burden during the pandemic. One recent scoping review identified that the prevalence of anxiety, depression, and stress widely varies based on the study methods, study settings, phase of the pandemic and instrument used to assess the measures ( 3 ). It found the prevalence of anxiety varied from 2.5% in North India to 53% in Bangladesh, depression varied from 3.5% in North Indian slum to 29.8% in Pakistan, and stress related symptoms varied from 18.3% in Pakistan to 59.7% in Bangladesh ( 3 ).…”
mentioning
confidence: 99%
“…One recent scoping review identified that the prevalence of anxiety, depression, and stress widely varies based on the study methods, study settings, phase of the pandemic and instrument used to assess the measures ( 3 ). It found the prevalence of anxiety varied from 2.5% in North India to 53% in Bangladesh, depression varied from 3.5% in North Indian slum to 29.8% in Pakistan, and stress related symptoms varied from 18.3% in Pakistan to 59.7% in Bangladesh ( 3 ).…”
mentioning
confidence: 99%